Visual and Textual Readings of Colonialism. José María López Sánchez y Miguel Ángel Puig-Samper Mulero (eds.). Introduction - López Sánchez, José María; Puig-Samper Mulero, Miguel Ángel (Hispania Nova, 2023)
This monograph is the result of activities planned within the Science, Racism and Visual Colonialism (Visualrace) project, ref. PID2020-112730GB-I00, funded by MCIN/AEI/ 10.13039/501100011033. However, as the knowledge enterprise has long needed to build alliances and networks to be fully successful, not all the authors of this dossier belong to this project and we are very pleased to be able to present some contributions that greatly enrich us "from outside" the project. The subject that concerns us, textual and visual readings of colonialism, is an issue that has received increasing attention in historiography in recent decades. Our approach focuses on the relationship between science and racism, with the immediate consequence of the discrimination of some of the populations that were the object of attention of this binomial.Translated with DeepL.com (free version)